Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan di PT Bogor ,Kabupaten Bogor Jawa Barat - Ahmad Solhani; Ahmad Zailani; Nisfatun Khasanah (Yayasan Literasi Sains Indonesia, 2022)
Training is part of education which concerns the learning process to acquire and improve skills outside the education system which prioritizes practice rather than theory, and where work discipline is a person's work ability to foster awareness and willingness to comply with all company regulations and social norms applicable in the company which can affect employee performance as seen from the work of these employees by showing the quality and quantity that have been achieved by employees in the Bogor area. And in this study the aim was to be able to determine the effect of training and work discipline on employee performance in the Bogor area both partially and simultaneously using quantitative methods, namely distributing questionnaires where a sample of 103 respondents was obtained and this study used data analysis techniques used was statistical analysis with classical assumption test, t-test hypothesis, f-test hypothesis, determination coefficient test to find out whether each variable influences each other or not,